Effects of Religious Versus Conventional Cognitive-Behavioral Therapy on Gratitude in Major Depression and Chronic Medical Illness: A Randomized Clinical Trial. Issue 2 (2nd April 2016) - Pearce, Michelle J.; Koenig, Harold G.; Robins, Clive J.; Daher, Noha; Shaw, Sally F.; Nelson, Bruce; Berk, Lee S.; Belinger, Denise; Cohen, Harvey Jay; King, Michael B.
ABSTRACT: This study examined whether religiously-integrated cognitive behavioral therapy (RCBT) was more effective than conventional CBT (CCBT) on generating gratitude among religious persons with major depressive disorder (MDD) and chronic medical illness (CMI). Participants at least somewhat religious/spiritual with MDD and CMI were randomized to receive 10 sessions of RCBT or CCBT. Both RCBT and CCBT predicted an increase in gratitude over time. Higher baseline religiosity predicted increases in gratitude among those receiving CCBT and RCBT. Higher levels of baseline gratitude predicted a faster decline in depressive symptoms independent of treatment group at 12 and 24 weeks.